Mental health correlates of athletic shame and guilt among elite-level youth athletes in Turkey - Lima, Y.; Öz, N. D.; Denerel, N.; Treeby, M. S.; Rice, S. (Journal of Science and Medicine in Sport, 2024)
Objectives This study evaluated the mental health correlates of athletic shame and guilt among elite-level youth athletes and provided psychometric data on the Turkish version of the Athletic Perceptions of Performance Scale.